Kajian Literature Review: Hubungan Peran Perawat Dalam Pencegahan Dan Perawatan Dengan Kejadian Dekubitus Pada Pasien Stroke - Faqih Zanik, Muhammad; Emilia Rosana, Marsa; Permata Pratiwi, Pina; Nuraeni, Selma; Juwita, Salwa; Sopiah, Popi; Ridwan, Heri (Universitas Haji Sumatera Utara, 2025)
Decubitus ulcer is a serious complication that often occurs in stroke patients with impaired mobility, which can worsen physical conditions and reduce quality of life. This study aims to examine the role of nurses in the prevention and care of decubitus in stroke patients through a multidisciplinary approach. The research method involved a literature review of relevant articles from 2014-2024. The results showed that preventive strategies, such as setting the sleeping position on the side, application of olive oil, massage with virgin coconut oil, and use of aloe vera gel, were significantly effective in reducing the incidence of decubitus. In addition, the education provided by nurses to the patient's family is crucial in improving family understanding and involvement in patient care at home. Collaboration between nurses and families allows for more optimal prevention of decubitus ulcers, thereby improving the quality of life of stroke patients. These findings highlight the importance of nurses' proactive role in decubitus prevention through a holistic and educative approach.